1961
DOI: 10.1002/cber.19610940819
|View full text |Cite
|
Sign up to set email alerts
|

Zur Struktur von Organoschwefelverbindungen, V. Oxydationskinetik einiger Arylsulfide und ‐sulfoxyde

Abstract: 2060KRESZE, SCHRAMM und CLEVE Jahrg. 94 getrocknet. Nach Verdampfen des Usungsmittels schied sich wenig 5-Hydroxy-3-phenyl-thiodiazol27) ab. vollstandiger nach Zugabe des doppelten Vol. Petrolather. Man filtrierte nach Stehenlassen Uber Nacht und destillierte. Nach dem Petrolilther ging zwischen 90 und 1 l0"/l7 Torr die Fluorverbindung Uber. Ausb. 7.1 g.Das Rohprodukt wurde in 50 ccm Methanol bei Raumtemperatur gelast und abgekuhlt.Bei -10 bis -20" lie0 man die Fluorverbindung durchkristallisieren, kUhlte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1961
1961
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Numerous oxidations of organosulfur compounds by hydroperoxidic reagents have been studied over the past five decades. [1][2][3][4][5][6][7][8][9][10][11][12][13] The early expectation was that the oxidation of sulfides would involve the formation of a sulfonium intermediate by S N 2 displacement of nucleophilic S upon the peroxo bond (Scheme 1a); 1 however, inconsistencies with this assumption became apparent. For example, reaction rates are strongly dependent neither on the relative permittivity of the solvent 2 nor on the ionic strength 3 as would be expected for a reaction involving a large separation of charge; on the other hand, reaction rates are strongly dependent on the protic nature of the solvent 4 and, if an aprotic solvent is used, the order of reaction in the hydroperoxide may increase from one to two.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous oxidations of organosulfur compounds by hydroperoxidic reagents have been studied over the past five decades. [1][2][3][4][5][6][7][8][9][10][11][12][13] The early expectation was that the oxidation of sulfides would involve the formation of a sulfonium intermediate by S N 2 displacement of nucleophilic S upon the peroxo bond (Scheme 1a); 1 however, inconsistencies with this assumption became apparent. For example, reaction rates are strongly dependent neither on the relative permittivity of the solvent 2 nor on the ionic strength 3 as would be expected for a reaction involving a large separation of charge; on the other hand, reaction rates are strongly dependent on the protic nature of the solvent 4 and, if an aprotic solvent is used, the order of reaction in the hydroperoxide may increase from one to two.…”
Section: Introductionmentioning
confidence: 99%
“…The stereochemistry of the esters (3) and (4) was deduced on the basis of the n.m.r. spectra of their corresponding 2-acetoxy derivatives (6) and (7). In an earlier paper,' we reported that the methyl signal of the acetoxy group of the threo-isomer (6a) appeared at higher field 7 Part of this study was presented at the 42nd Symposium on Synthetic Organic Chemistry (Japan), Tokyo, November, 1982.…”
Section: Resultsmentioning
confidence: 97%
“…C,,H,,NO,S, M = 363.39, triclinic, a = 7.728 1 (6), b = y = 102.544(9)", U = 861.q1) A3, D , = 1.402 g ~m -~, Z = 2, F(O00) = 380, Space group PI. 16.5740(15), c = 7.152 2(5) A, a = 103.623 (8), p = 79.640 (7), Crystallographic Measurements and Structure Analysis.-The intensities and cell dimensions were obtained from a Rigaku four-circle diffractometer (AFC-V) by an 28 -o scan with graphite-monochromated Cu-K, radiation. Of 2 943 reflections, measured to a maximum 28 of 130°, 2 351 had I > 2.67 o(Z) and were considered observed.…”
Section: X-ray Crystallographic Analysis Ofmentioning
confidence: 99%
“…Loss of the guest is accompanied by conversion to the higher-melting 0 OA = open air, CC = closed container. 6 ! Melting points : all clathrates were similar initially and covered a broad range fide supra).…”
Section: Discussionmentioning
confidence: 99%